EVALUATION OF THE IMPLEMENTATION OF HOSPITAL HEALTH PROMOTION STANDARDS (PKRS) AT SINAR HUSNI HOSPITAL IN 2025 - Suzan Fhitriana Pakpahan; Roni Gunawan; Dwi Ana Putri (Program Pascasarjana UIN Sumatera Utara, 2026)
PKRS is an appropriate program for providing education to improve the quality of healthcare services in hospitals. Implementing PKRS not only improves service quality but also meets national and international hospital accreditation standards. Purpose; The purpose of this study was to determine the compliance of health promotion standards at Sinar Husni HOSPITAL in 2025. Method; The research method used a qualitative method with a case study approach. Thirteen informants were used. Data were collected through in-depth interviews. Analysis used data reduction, data display, and conclusion drawing. Results; The study showed that the implementation of Standard I had not yet developed guidelines for a hospital strategic plan, the PKRS team did not meet the required standards for management staff, special funds were not available, and facilities and infrastructure for PKRS implementation were available but did not meet minimum standards. Implementation of Standard II: The health promotion needs assessment has not been carried out, and there is no reporting to the source/community partner for PKRS implementation. Implementation of Standard III: The implementation of health promotion interventions for patients and their families has not been implemented and there is no recording in the medical record. Implementation of Standard IV: There is no follow-up plan for the evaluation results. Conclusion; The implementation of hospital health promotion standards at Sinar Husni Hospital does not comply with the standards set out in the Indonesian Minister of Health Regulation No. 44 of 2018. Therefore, it is recommended that a presentation related to PKRS be made in the hospital's strategic plan, the PKRS team be expanded, and the requirements for becoming a PKRS manager be met.